Ta'līm al-Qawāʿid al-Naḥwiyyah bi Istikhdām Naẓariyyat al-Taʿallum al-Maʿrifiyyah fī Sunan Drajat Lamongan - Syarifah, Hilyah; Hilmi, Danial (UAS PRESS, 2024)
The implementation of Nahwu's qawaid learning through David Ausubel's cognitive theory at MA Muallimin Muallimat Sunan Drajat Lamongan considering both supporting and inhibiting factors. This article aims to understand how Nahwu's qawaid learning is implemented using David Ausubel's cognitive theory at MA Muallimin Muallimat Sunan Drajat Lamongan and the factors influencing its implementation. Using a qualitative case study method, data was collected from madrasa heads, Nahwu and Study Text teachers, students, and related documents. Data collection techniques included interviews, observations, and documentation. Data analysis used Miles and Huberman's techniques and triangulation for validity. The research found that Nahwu qawaid learning aligns with Ausubel's cognitive theory principles, including advance organizer, progressive differentiation, superordinate learning, and integrative reconciliation. Supporting factors include Study Text subjects for direct practice, skilled teachers, and the use of the Turats book. Inhibiting factors are varying student abilities and focus challenges due to numerous subjects and activities.